Características de consumo del Rituximab en el servicio de Reumatología del Hospital Víctor Lazarte Echegaray La Libertad, Enero-Diciembre del 2016 - Minchola Zenozain, Jackeline Thatiana (2017)
The present report evaluated the consumption characteristics of Rituximab in the Rheumatology department of Hospital Víctor Lazarte Echegaray - EsSalud. A descriptive, cross - sectional and retrospective study of drug use was carried out, including patients hospitalized in the Rheumatology Service during January - December 2016. The Prescribed Daily Dose System (PDD) was used as a unit of measurement of consumer spending included in this period. The study had a total of 60 patients, with demographic data corresponding to 26.67% of the consumption of Rituximab in female patients, with ages ranging from 61 to 70 years, in the case of the% of consumption units of Rituximab showed an increase in the last three months with percentages 13.19% of consumption units, which is why the average consumption expressed in daily dose prescribed DDP is 2 158.92 DDP, presenting an annual consumption cost of S/. 662 167.2 corresponding to the study time. This fact makes it necessary to assess the expenditure generated by these drugs as an important variable, due to the increase in recent years and in terms of safety and cost-benefit, although its cost is higher, it has the advantage of reducing costs Associated with medical visits and hospitalizations, without forgetting the costs associated with disability and unemployment